2017
DOI: 10.1002/jctb.5465
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic strategies for microbial glycerol overproduction

Abstract: Glycerol as a platform chemical has wide applications in chemical, pharmaceutical, and food industries and is a useful feedstock for the production of bio‐based chemicals. There is an increasing demand for sustainable glycerol production and microbial glycerol production is a promising alternative. The paper highlighted this new trend and summarized recent research progress on microbial glycerol production, and focused mainly on the efforts achieved in rational design of S. cerevisiae, as well as Escherichia c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 35 publications
2
6
0
Order By: Relevance
“…It is used on a large scale in the pharmaceutical and cosmetic industries, by the paints and dyes industry as a raw material for the synthesis of many chemical compounds (e.g. nitroglycerin, polymers), and in biosurfactants (Taherzadeh et al, 2002;Lim et al, 2018). With an increase in demand for fuels obtained from biomass the amount of glycerine waste is increasing.…”
Section: Introductionmentioning
confidence: 99%
“…It is used on a large scale in the pharmaceutical and cosmetic industries, by the paints and dyes industry as a raw material for the synthesis of many chemical compounds (e.g. nitroglycerin, polymers), and in biosurfactants (Taherzadeh et al, 2002;Lim et al, 2018). With an increase in demand for fuels obtained from biomass the amount of glycerine waste is increasing.…”
Section: Introductionmentioning
confidence: 99%
“…As described in the introduction, cells of E. coli are not known to form and excrete glycerol when growing on glucose [ 38 , 39 ]. As we showed that GL3/pJF119 fsaA A129S ( Figure 5 ), and to a lesser extent also GL4 ( Table 4 ), excrete DHA during growth on glucose, we intended to stop the observed catabolism of DHA in order to favor DHA and glycerol formation from sugars.…”
Section: Resultsmentioning
confidence: 99%
“…DHA is an ingredient in many self-tanning compounds and glycerol is a carbon source which has received much attention as it can be used for production of many added-value compounds (for references see [ 36 ]). In contrast to other microorganisms such as yeast [ 37 ], cells of E. coli are not known to form and excrete glycerol when growing on glucose [ 38 , 39 ]. By introduction of genes from yeast which encode enzymes for the conversion of DHAP to glycerol, however, E. coli glycerol producers had been constructed [ 40 , 41 , 42 , 43 ]; eventually this has led to recombinant E. coli cells forming 1,3-propanediol from glucose via the intermediate glycerol.…”
Section: Introductionmentioning
confidence: 99%
“…The RPL18A gene encodes a member of the L18AE family of ribosomal proteins, which is a component of the 60S subunit[14]. The TPI1 gene encodes an enzyme composed of two identical proteins that catalyzes the isomerization of glyceraldehyde 3-phosphate (G3P) and dihydroxy-acetone phosphate (DHAP) in glycolysis and gluconeogenesis[15]. Von Willebrand Factor A Domain Containing 5B2 (VWA5B2) is a protein-coding gene.…”
Section: Discussionmentioning
confidence: 99%